Peripheral Neuropathy and Associated Factors in Diabetics at the CNHU-HKM of Cotonou in 2021 - KEREKOU HODE, ANNELIE; DEDJAN, A Hubert; SONDJO, Martine (My University, 2023)
Diabetic peripheral neuropathy (DPN) is a common complication of diabetes. The main objective of the study was to determine the prevalence of diabetic peripheral neuropathy and associated factors in diabetics in the University Clinic of Endocrinology Metabolism Nutrition of the CNHU-HKM, Cotonou, Benin 2021. This was a cross-sectional, analytical study that ran from 23 September to 23 December 2021. Admitted diabetic patients seen in consultation during the study period were included. The DN4 tool was used as the basis for data collection. Data analysis was performed using R software version 3.6.1. Multivariate analysis was used to identify factors associated with DPN. Out of 155 diabetics, 54 patients had diabetic peripheral neuropathy, a prevalence of 34.8%. The average age of our patients was 56.8 years and 56.8% were female. Of the patients, 54.7% had unbalanced diabetes. An association between DPN and gender (p = 0.022), occupation (p = 0.004), education (p = 0.011), hypertension (p = 0.017), smoking (p = 0.031), diabetic imbalance (p = 0.001), diabetic retinopathy (p = 0.020) and dyslipidaemia (p = 0.015) was observed. DPN was also associated with erectile dysfunction in men (p = 0.001). Conclusion: Diabetic peripheral neuropathy is common (34.8). Its occurrence is indicative of the presence of associated factors
Keywords: Diabetes; Diabetic Peripheral Neuropathy; DN4 Questionnaire; Associated; Factors; Benin